2019
DOI: 10.1152/ajpendo.00543.2018
|View full text |Cite
|
Sign up to set email alerts
|

Compensation for cold-induced thermogenesis during weight loss maintenance and regain

Abstract: Prevalence of obesity is exacerbated by low rates of successful long-term weight loss maintenance (WLM). In part, relapse from WLM to obesity is due to a reduction in energy expenditure (EE) that persists throughout WLM and relapse. Thus, interventions that increase EE might facilitate WLM. In obese mice that were calorically restricted to reduce body weight by ~20%, we manipulated EE throughout WLM and early relapse using intermittent cold exposure (ICE; 4°C, 90 min/day, 5 days/wk, within the last 3 h of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…The half‐life of catecholamines, however, is quite short, meaning the anorexic state recedes quickly after removal of the stimulus. This is demonstrated, as mentioned above, by rodents rapidly decreasing body mass during intermittent CE and regaining it upon return to thermoneutral conditions, creating a daily flux in body weight.…”
Section: Cold Exposure Circulating Appetite‐related Peptides and Thmentioning
confidence: 73%
See 1 more Smart Citation
“…The half‐life of catecholamines, however, is quite short, meaning the anorexic state recedes quickly after removal of the stimulus. This is demonstrated, as mentioned above, by rodents rapidly decreasing body mass during intermittent CE and regaining it upon return to thermoneutral conditions, creating a daily flux in body weight.…”
Section: Cold Exposure Circulating Appetite‐related Peptides and Thmentioning
confidence: 73%
“…Feeding time also increased significantly for rodents in these two studies, as food was made available in ad libitum quantities; therefore, the rodents did not have to forage. A third study also found that intermittent (i.e., part day) CE resulted in increased EE during the exposures, but to a compensatory decrease in EE when returned to room temperature that resulted in no changes in body weight . Exposing mice (C57BL/6J) to intermittent CE 3 days per week also stimulated EI and decreased leptin with exposure times of as little as 4 hours per day but resulted in no changes in body mass.…”
Section: Cold Exposure In Animalsmentioning
confidence: 87%
“…Additionally, exercise training has been shown to potentiate sympathetic signaling after weight loss (10, 44), which may impact total energy expenditure with a bout of overfeeding. However, increasing adipose uncoupling protein 1 expression or activating the sympathetic nervous system does not appear to increase energy expenditure during weight regain (12,30). Regardless, further analyses of these tissues and mechanisms are required to dissect their importance during weight regain.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there was a significant decrease in white adipose tissue in C57BL/6 mice following sustained cold exposure [ 30 ], but not in rats ( Rattus norvegicus ) [ 31 ]. Furthermore, researchers have observed varying effects in laboratory mice ( Mus musculus ) subjected to intermittent cold, with no change in fat deposits found for one study [ 32 ], and others finding an increase [ 33 , 34 ] or a decrease [ 35 ]. In the wild, small mammals may be exposed more frequently to repetitive or intermittent cold temperatures than to persistent cold temperatures.…”
Section: Introductionmentioning
confidence: 99%